A retrospective cohort study of the association of anesthesia and hernia repair surgery with behavioral and developmental disorders in young children - DiMaggio, Charles (2009)
Recent animal studies have shown that commonly used anesthetic agents may have serious neurotoxic effects on the developing brain. The purpose of this study was to assess the association between surgery for hernia repair and the risk of behavioral and developmental disorders in young children. We performed a retrospective cohort analysis of children who were enrollees of the New York State Medicaid program. Our analysis involved following a birth cohort of 383 children who underwent inguinal hernia repair during the first three years of life, and a sample of 5050 children frequency-matched on age with no history of hernia-repair before age 3. After controlling for age, gender, and complicating birth-related conditions such as low birth weight, children who underwent hernia repair under three years of age were more than twice as likely as children in the comparison group to be subsequently diagnosed with a developmental or behavioral disorder (adjusted HR 2.3, 95% CI 1.3, 4.1). Our findings add to recent evidence of the potential association of surgery and its concurrent exposure to anesthetic agents with neurotoxicity and underscore the need for more rigorous clinical research on the long-term effects of surgery and anesthesia in children.